Integrasi Interkoneksi Metode Bimbingan Konseling Islam Berlandasan Hadis Nabawi - Riadatul Jannah; Irsyadunnas (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah IAI Miftahul Ulum Pamekasan, 2024)
The Prophet’s Hadith is everything that is given from the Prophet SAW both in the from of eords, deeds, takrir, nature and things about the Prophet. The purpose of this study is to determine the integration of Islamic Counselig Guidance Based on the Prophet’s Hadith. The method used in this study is a literature review. Islamic Counseling Guidance methods that are relevant as Islamic Counseling Guidance methods include interview methods, advice methods, home visit methods.